How do ex-ante severance pay contracts fit into optimal executive incentive schemes? - RAU, P. RAGHAVENDRA; XU, JIN (Journal of Accounting Research, 2012)
We analyze a sample of over 3,600 ex ante explicit severance pay agreements in place at 808 firms and show that firms set ex ante explicit severance pay agreements as one component in managing the optimal level of equity incentives. Younger executives are more likely to receive explicit contracts and better terms. Firms with high distress risk, high takeover probability, and high return volatility are significantly more likely to enter into new or revised severance contracts. Finally, ex post payouts to managers are largely determined by the ex ante contract terms.